2020
DOI: 10.1128/mra.00136-20
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Mercury-Resistant Serratia sp. Strain SRS-8-S-2018

Abstract: A mercury (Hg)-resistant Serratia sp. strain, SRS-8-S-2018, was isolated, followed by generation of its draft genome sequence, which indicated a genomic size of 5,323,630 bp composed of 5,261 coding sequences. A suite of genomic functions in strain SRS-8-S-2018 was identified, and these likely facilitate survival in a metalliferous soil habitat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…( n = 11) and Penicillium spp. ( n = 8) being dominant; some of these groups have also been identified as predominant groups in metagenomic analyses ( 7 , 8 ), including our work on this aspect ( 5 , 9 , 10 ). Some other groups retrieved as higher representatives included Pseudomonas ( n = 4), Bradyrhizobium ( n = 4), Burkholderia ( n = 3), Serratia ( n = 3), and Lepidosphaeria ( n = 3).…”
Section: Announcementmentioning
confidence: 54%
See 1 more Smart Citation
“…( n = 11) and Penicillium spp. ( n = 8) being dominant; some of these groups have also been identified as predominant groups in metagenomic analyses ( 7 , 8 ), including our work on this aspect ( 5 , 9 , 10 ). Some other groups retrieved as higher representatives included Pseudomonas ( n = 4), Bradyrhizobium ( n = 4), Burkholderia ( n = 3), Serratia ( n = 3), and Lepidosphaeria ( n = 3).…”
Section: Announcementmentioning
confidence: 54%
“… a Note that all strains were isolated on plates containing 2 mM uranium and hence are U resistant. Some strains, designated by an asterisk (*), were chosen for additional MIC assessment based on their predominance in the metalliferous SRS soils ( 5 , 9 , 10 ). …”
Section: Announcementmentioning
confidence: 99%
“…Despite this advantage of microbially based heavy metal bioremediation, studies have also unequivocally shown that bacteria can acquire antibiotic resistance when exposed to long-term contamination, especially with Hg and U ( Benyehuda et al, 2003 ), including our previous work ( Agarwal et al, 2019 , 2020a , b ; Gendy et al, 2020a , b ; Pathak et al, 2020 ). This builds upon significant evidence that exists on the SRS soils which unequivocally shows higher levels of antibiotic resistance in contaminated SRS soils relative to reference soils ( Stepanauskas et al, 2006 ; Wright et al, 2006 ; Thomas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 84%
“…Heavy metal contamination is a global environmental problem shown to cause both ecological and public health problems ( Tchounwou et al, 2012 ). However, ecosystems with pervasive and long-term heavy metal contamination, such as the Savannah River Site (SRS), located in Aiken, SC, United States, are known to harbor metal-resistant microorganisms, which have acquired genomic features to resist and circumvent metal toxicity ( Ye, 2014 ; Agarwal et al, 2018 ; Pathak et al, 2019 , 2020 ; Gendy et al, 2020a , b ). The two main heavy metal contaminants within the impacted SRS soils include mercury (Hg) and uranium (U) ( Sowder et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation